200k views
2 votes
Consider the expression below.

(a + 4)(a + 9)
For (x + 4)(x + 9) to equal 0. either (x + 4) or (x + 9) must equal
The values of x that would result in the given expression being equal to o, in order from least to greatest, are
and


User Larsemil
by
4.7k points

1 Answer

2 votes

Answer:

x = - 9, x = - 4

Explanation:

Set (x +)(x + 9) equal to zero, that is

(x + 4)(x + 9) = 0

Equate each factor to zero and solve for x

x + 4 = 0 ⇒ x = - 4

x + 9 = 0 ⇒ x = - 9

Thus

x = - 9, x = - 4

User Ben Everard
by
4.8k points